Pathogenetic Mechanisms And Contemporary Management Of Disseminated Intravascular Coagulation (Eurasian Research Bulletin, 2025)
A defining characteristic of disseminated intravascular coagulation (DIC)—an acquired syndrome arising in the context of severe illness—is the widespread activation of coagulation pathways within the vasculature, culminating in extensive fibrin deposition throughout the circulatory system. This dysregulated hemostatic response not only precipitates microvascular thrombosis and subsequent tissue ischemia but also exhausts platelets and clotting factors, leading to paradoxical bleeding. Moreover, the interplay between procoagulant stimuli and impaired fibrinolysis amplifies organ dysfunction, underscoring the importance of comprehensive laboratory assessment (including D‑dimer, fibrinogen levels, and thrombin–antithrombin complexes) and the early institution of targeted therapies—such as anticoagulants, natural anticoagulant supplementation, and supportive transfusions—to restore hemostatic balance and improve clinical outcomes.